2018
DOI: 10.1186/s12884-018-1903-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of maternal near miss among women admitted in Gurage zone hospitals, South Ethiopia, 2017: a case control study

Abstract: BackgroundMaternal mortality and morbidity remain unacceptably high in developing countries. Behind every maternal death, many other women suffered from acute and chronic obstetric complications. Women who survive severe acute maternal morbidities/near miss have many characteristics in common with maternal death events particularly on risk factors. Ethiopia is among countries with high maternal mortality and morbidities in sub-Saharan Africa. However there is scarce evidence on risk factors of severe acute mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
28
2
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 31 publications
10
28
2
9
Order By: Relevance
“…Likewise, the present study revealed that near-miss cases women were more likely to have a first delay (delay in deciding for health care) than their counterparts. This is in line with studies done in Morocco, Ile-Ife Nigeria, and Ethiopia [19,26,31]. Whereas second and third delays were not significantly associated with maternal near miss.…”
Section: Discussionsupporting
confidence: 91%
“…Likewise, the present study revealed that near-miss cases women were more likely to have a first delay (delay in deciding for health care) than their counterparts. This is in line with studies done in Morocco, Ile-Ife Nigeria, and Ethiopia [19,26,31]. Whereas second and third delays were not significantly associated with maternal near miss.…”
Section: Discussionsupporting
confidence: 91%
“…unnecessary C-section) in the middle-and low/middle-income countries exposes females to increased risk (24). According to the literature, females with previous C-section are more prone to SMO due to the increased risk of uterine rupture after vaginal birth and severe bleeding (25). In line with previous studies, disease susceptibility and proneness to severe pregnancy complications may partly explain the high prevalence of MNM in this hospital (26,27).…”
Section: Discussionsupporting
confidence: 78%
“…In many low-and middle-income countries, obstetric haemorrhage is the leading cause of serious maternal morbidity and mortality [22]. Obstetric haemorrhage accounted for approximately 26-46% of the MNM cases in Ethiopian women [18,23]. In this study, we determined the association between severe postpartum haemorrhage and CD.…”
Section: Discussionmentioning
confidence: 99%